A Rare Case of Giant Endometrial Polyp with Hematometra with Old Healed Endometriotic Lesions : A Case Report (Global Journal of Medical Research, 2019)
Giant endometrial polyp with hematometra with old healed endometriotic lesion is a rare case. We present a case of old patient presented with complaint of pain in lower abdomen, but after clinical evaluation , USG and MRI report, the case diagnosed early as endometrial polyp, incidentally find hematometra and old healed endometriotic lesion at the time of hysterectomy.
Keywords: endometrial polyp; hematometra; endometriosis